2006
DOI: 10.2175/106143005x90065
|View full text |Cite
|
Sign up to set email alerts
|

Cycling of Volatile Organic Sulfur Compounds in Anaerobically Digested Biosolids and its Implications for Odors

Abstract: The objectives of this research were to elucidate the mechanisms for production and degradation of volatile organic sulfur compounds (VOSCs), key odor causing compounds produced by biosolids. These compounds included methanethiol (MT), dimethyl sulfide (DMS), and dimethyl disulfide (DMDS). A series of experiments were used to probe various pathways hypothesized to produce and degrade these VOSCs. The production of MT was found to mainly occur from degradation of methionine and the methylation of hydrogen sulfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
117
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(127 citation statements)
references
References 40 publications
10
117
0
Order By: Relevance
“…Previous studies have demonstrated an interaction between methanogens and S emission probably caused by the ability of methanogens to demethylate organic S compounds (Higgins et al, 2006;Eriksen et al, 2010). A similar interaction was not evident in our data, although at Day 27 methanogenic activity, as revealed by high CH 4 emission rates in +CaCl 2 and +BA+CaCl 2 treatments, was accompanied by low MT and DMS emission levels.…”
Section: Sulfur Turnoversupporting
confidence: 75%
“…Previous studies have demonstrated an interaction between methanogens and S emission probably caused by the ability of methanogens to demethylate organic S compounds (Higgins et al, 2006;Eriksen et al, 2010). A similar interaction was not evident in our data, although at Day 27 methanogenic activity, as revealed by high CH 4 emission rates in +CaCl 2 and +BA+CaCl 2 treatments, was accompanied by low MT and DMS emission levels.…”
Section: Sulfur Turnoversupporting
confidence: 75%
“…Immediately after extraction from the PETE bottles, analytical testing for selected odorants in headspace gases were analyzed Bucknell University using GC-MS and GC equipped with flame ionization detector gas analyses using the methodology described by Higgins et al (2006). The remaining volumes were collected in Tedlar ™ bags, diluted 100x with odorless nitrogen gas in 10-L Tedlar ™ bags and evaluated at the Penn State Odor Assessment laboratory within 4 hours.…”
Section: Laboratory Olfactometry and Analytical Testingmentioning
confidence: 99%
“…Higgins et al (2006Higgins et al ( , 2008 have shown that during "staging" (1-day to 10-days holding time) of dewatered biosolids cake, there is an initial production of high concentrations of total volatile organic sulfur compounds (TVOSCs), including: methyl…”
mentioning
confidence: 99%
“…Industrial sources of RSCs include fugitive emissions (leakages) from the steel industry, pulp and 55 paper mills, refineries, incinerators, landfills, and sewage treatment facilities. Higgins et al 2006 [7] studied the mechanisms for production and degradation of sulfur compounds, key molecules that cause odor produced by biosolids. Additionally, their chemistry in the atmosphere has significant implications for global climate changes by impact radiative forcing, ozone layer depletion and the acidity of precipitation [8].…”
Section: Introductionmentioning
confidence: 99%